Complement induces a transient increase in membrane permeability in unlysed erythrocytes. - Halperin, J A (1988)
The effects of low concentrations of human serum on antibody-sensitized sheep erythrocytes (EA) were studied. We report that exposure to low concentrations of serum induced a large but transient increase in the membrane permeability of those EA that do not lyse. This change in the permeability of the erythrocyte membrane resulted in net uptake of Na+ and decrease in cell K+, without affecting the total internal cation content. Although exposure to serum also allowed for net uptake of larger molecules like L-glucose, it did not lead to cell swelling. Experiments with sera genetically deficient in one of the terminal complement components showed that C8, but not C9, was required to produce the observed change in membrane permeability. Therefore, we propose that the C5b-8 complex can mediate the transient increase in permeability observed in unlysed erythrocytes during complement activation by whole serum.